2012
DOI: 10.17660/actahortic.2012.934.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Appropriate Postharvest Technologies for Small Scale Horticultural Farmers and Marketers in Sub-Saharan Africa and South Asia - Part 1. Postharvest Losses and Quality Assessments

Abstract: Part 1 of 2. The objectives of the study were 1) to systematically assess and characterize postharvest losses for key horticultural crops in four countries using field based measurements at the farm, wholesale and retail markets, to increase the knowledge base and identify priority postharvest problems that currently limit market access for small farmers and rural marketers, 2) to identify and field test postharvest technology options that could solve priority postharvest problems by conducting field trials in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 9 publications
2
48
0
Order By: Relevance
“…In a study by Kitinoja and AlHassan (2012), it was found that temperatures for leafy vegetables harvested in Rwanda and Benin were generally higher than those recommended for quality maintenance [8]. Pulp temperatures for temperate crops, including amaranth, which were handled without care for shading or temperature control, were found to be 25-30 °C above the recommended lowest safe handling temperatures of 0-2 °C.…”
Section: Temperature and Relative Humidity Within Clamshell Packagesmentioning
confidence: 97%
See 4 more Smart Citations
“…In a study by Kitinoja and AlHassan (2012), it was found that temperatures for leafy vegetables harvested in Rwanda and Benin were generally higher than those recommended for quality maintenance [8]. Pulp temperatures for temperate crops, including amaranth, which were handled without care for shading or temperature control, were found to be 25-30 °C above the recommended lowest safe handling temperatures of 0-2 °C.…”
Section: Temperature and Relative Humidity Within Clamshell Packagesmentioning
confidence: 97%
“…In the study on storage of leafy vegetables conducted in Rwanda, Kitinoja and AlHassan (2012) found that mean weight loss on the farm for 10 samples of amaranth packed in sacks was 10.8% ± 9.1% over up to 240 min directly after harvest [8]. During 6 h display at a retail market, the additional mean weight loss in bunches of amaranth was 11.3% ± 2.8%.…”
Section: Weight Lossmentioning
confidence: 99%
See 3 more Smart Citations